Culture. Science. Education: Current Issues - Kuklina A. S., Kuklina I. G., Lesokhina A. M., Shchankina L. N., Gutova S. G., Kholopova A. K., Balan A. V., Pisareva E. V., Shevchenko E. I., Berezkina I. V., Malkanduev I. A., Khanbabaeva O. E., Kvashnin P. R., Makhkamova S. I., Rezak E. V., Sabodina E. P., Melnikov Y. S., Mikhalchenkova N. A., Bolshakov S. N., Bolshakova I. M., Kulikova N. V., Krasilnikova S. V., Arshinik S. P., Lysenko V. V., Kostenko E. G. (Culture. Science. Education: Current Issues, 2020)
the most relevant features of the French Enlightenment are studied in the article. One of the features is ambivalence, that was expressed in most of the theoretical judgments by representatives of the era. The main ideas of the French Enlightenment are presented through the prism of the historical formation of the basic concepts: nature, human brain, culture. It is emphasized that the main achievement of the enlighteners in the cultural reformation of society was to combat religious and moral prejudices. It is noted that the value of enlighteners is in their innovative attempt to create a progressive model of cultural development based on a naturalistic and mechanical and deterministic picture of the world. The philosophical and cultural analysis revealed the internal dynamics of the enlighteners' ideas from civilizational optimism to criticism of civilizational progress. It is concluded that the philosophical and theoretical legacy of the Enlightenment, in the framework of the development of a single paradigm, is integral, logical and actually complete, that made the most use of its methodological and heuristic potential.
Keywords: просвещение; культура; общество; enlightenment; идеология; society; природа; culture; ideology; рационализм; французские просветители; энциклопедизм; общественный прогресс; rationalism; French enlighteners; nature; encyclopedism; social progress